2016
DOI: 10.3895/rbqv.v8n2.3990
|View full text |Cite
|
Sign up to set email alerts
|

Estilo de vida de universitários residentes em moradia estudantil

Abstract: OBJETIVO: Comparar os indicadores de estilo de vida em grupo de estudantes com melhor e pior escore de percepção da QV reportada por jovens universitários que residem em moradia estudantil. MÉTODOS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Other results have shown that the environment receives the lowest score in studies conducted on university students in Brazil [16,17,18,19] . This fact can be attributed to the living conditions of Brazilians with high demands on a national level related to physical security, health, schooling and reduced opportunity and time for leisure activities [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Other results have shown that the environment receives the lowest score in studies conducted on university students in Brazil [16,17,18,19] . This fact can be attributed to the living conditions of Brazilians with high demands on a national level related to physical security, health, schooling and reduced opportunity and time for leisure activities [20] .…”
Section: Discussionmentioning
confidence: 99%